Kebijakan Pelayanan Pertanahan Yang Berkeadilan Gender Di Kota Semarang - Muhammad Dimas Aditya (Jurnal Impresi Indonesia, 2025)
This study examines land administration policies in Semarang City with a focus on gender justice. The main issue addressed is how land policies can provide fair and equal services for both men and women. This research employs a normative method by analyzing laws and regulations related to land services and gender justice principles, as well as evaluating their application in the context of Semarang City. The findings indicate that although regulations supporting gender equality exist normatively, their implementation still faces several challenges, such as the lack of gender perspective in technical policies and limited public outreach. Therefore, this study recommends the formulation of more gender-responsive policies and improved understanding among land administration officials regarding gender equality issues. Through a legal approach grounded in gender justice, land services are expected to become more inclusive and uphold the rights of all citizens without discrimination.